PRAKTEK INSIDER TRADING DALAM TRANSAKSI EFEK DI PASAR MODAL DAN UPAYA PENCEGAHANNYA MELALUI PENERAPAN PRINSIP KETERBUKAAN (DISCLOSURE PRINCIPLE) - ANDINA TAMPUBOLON (PREMISE LAW JURNAL, 2015)
Economic development of a country is highly determined by Banking and financial institutions, including capital market. The benefit of capital market is by providing financial source (long term) for businesses and at the same time  allocating capital resources optimally, providing investment facility for investors and at the same time making it possible to be verified, and providing leading indicator and economic trend for the State. The research used judicial normative approach. The attempt to forestall the incidence of insider trading in the Indonesian capital market is by tightening the regulation for the transparency of material information for all companies which want to do their stock transaction in the Indonesian capital market. It is recommended that OJK, which has the authority to determine whether or not a company is qualified to do stock transaction in the Indonesian capital market, be firm and impartial to all companies which want to do their stock transaction in the Indonesian capital market, especially in checking and supervising all material information of the companies which are qualified and healthy to do stock transaction in the Indonesian market. Keywords: Insider Trading, Disclosure, Indonesian Capital Market